Analisis Risiko Pengelolaan Sekolah Dalam Peningkatan Mutu Pendidikan - Huda, Atiqah Miftahul; Irsyad, Irsyad; Setiawati, Merika (CV. ITTC INDONESIA, 2025)
Efficient management of educational institutions is an important element for raising educational standards. However, various challenges can hinder these quality improvement efforts. This research aims to examine various challenges in the management of educational institutions and their impact on the quality of education. The method used in this research is a qualitative approach by collecting data through observation, in-depth interviews and document searches in several schools. The research results revealed five main risk categories: risks related to human resources, financial risks, facilities and infrastructure risks, risks related to management, and external risks. Findings suggest that more active risk management could reduce adverse impacts on educational quality. This research suggests developing an integrated risk management system in institutional management to ensure continuous improvement in the quality of education.